2015
DOI: 10.15698/mic2015.02.190
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Bax Inhibitor-1 inhibits cell death induced by pokeweed antiviral protein in Saccharomyces cerevisae

Abstract: Apoptosis is an active form of programmed cell death (PCD) that plays critical roles in the development, differentiation and resistance to pathogens in multicellular organisms. Ribosome inactivating proteins (RIPs) are able to induce apoptotic cell death in mammalian cells. In this study, using yeast as a model system, we showed that yeast cells expressing pokeweed antiviral protein (PAP), a single-chain ribosome-inactivating protein, exhibit apoptotic-like features, such as nuclear fragmentation and ROS produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Previous studies have reported the roles of BI1 in biotic and abiotic stress. Bax inhibitor 1 (BI1) is a conserved ER protein, suppressing cell death in animals and plants and regulating a cell death pathway, which is important for cell preservation during ER stress [ 55 , 56 , 57 , 58 , 59 ]. AtBI1 was rapidly up-regulated during wounding and pathogen challenge and restricted Plantago asiatica mosaic virus (PlAMV) and Turnip mosaic virus (TuMV) infection in A. thaliana [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the roles of BI1 in biotic and abiotic stress. Bax inhibitor 1 (BI1) is a conserved ER protein, suppressing cell death in animals and plants and regulating a cell death pathway, which is important for cell preservation during ER stress [ 55 , 56 , 57 , 58 , 59 ]. AtBI1 was rapidly up-regulated during wounding and pathogen challenge and restricted Plantago asiatica mosaic virus (PlAMV) and Turnip mosaic virus (TuMV) infection in A. thaliana [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The moderate content of ROS is considered to mediate the induction of defense pathways and help plants adapt to the changing environment ( Cruz de Carvalho, 2008 ). However, if stress continues to aggravate, the increase of ROS will lead to the damage of nucleic acids, proteins, lipids and other cellular components in plants, and causes programmed cell death (PCD) ( Çakır and Tumer, 2015 ). The conserved cell death suppressor Bax inhibitor-1 (BI-1) encoded by Zm00001d053952 plays a role in the downstream of PCD signaling and inhibits cell death.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results showed that yeast cells expressing PAP exhibited apoptotic-like features, such as nuclear fragmentation and production of reactive oxygen species (ROS). Arabidopsis thaliana Bax inhibitor-1, a plant antiapoptotic protein, which inhibits Bax induced cell death reduced the cytotoxicity of PAP in yeast, without affecting ribosome depurination and translation inhibition [ 32 ]. These results provided further evidence that ribosome depurination and translation inhibition by PAP could be separated from cytotoxicity.…”
Section: Cytotoxicity Of Papmentioning
confidence: 99%